The Effect of Foliar Putrescine Application, Ammonium Exposure, and Heat Stress on Antioxidant Compounds in Cauliflower Waste - Jacinta Collado-González; Maria Carmen Piñero; Ginés Otálora; Josefa López-Marín; Francisco M. del Amor (MDPI AG, 2021)
This work has been focused on the study of how we can affect the short heat stress on the bioactive compounds content. Some recent investigations have observed that management of nitrogen fertilization can alleviate short-term heat effects on plants. Additionally, the short-term heat stress can be also ameliorated by using putrescine, a polyamine, due to its crucial role in the adaptation of plants to heat stress Therefore, different NO3−/NH4+ ratios and a foliar putrescine treatment have been used in order to increase tolerance to thermal stress in order to take advantage of the more frequent and intense heat waves and make this crop more sustainable. So, other objective of this work is to make the cauliflower waste more attractive for nutraceutical and pharmaceutical preparations. Thus, the effect of a thermal stress combined with a 50:50 NO3−/NH4+ ratio in the nutrient solution, and the foliar application of 2.5 mM putrescine increased in the content of various sugars (inositol, glucose, and fructose), total phenolic compounds and polyamines, as well as in the antioxidant activity. The greatest accumulation of these compounds was observed in young leaves. Our results show from a physiological and agronomic point of view, that the foliar application of putrescine and the 50:50 NO3−/NH4+ treatment managed to alleviate the negative effects of the abiotic stress suffered at high temperature, yielding plants with higher antioxidant compounds content.